Health Status of Instutionalized Elderly: Morbidity Due to Oral and Dental Diseases - Mihaela Monica Scutariu; Ioana Dana Alexa (Romanian Society of Oral Rehabilitation, 2011)
The elderly patient represents a challenge for the dentist due to his physical and pathological features, elements that must be taken into consideration along with the associated diseases and the possible emotional fragility mainly caused by retirement and the eventual marginalization within the family. The transfer of the elderly person to a retirement home generates even more serious problems because of the risk that he might feel marginalized and abandoned or because of the adjustment problems that might arise. Our study was performed in November 2010 at the Retirement Home Copou and it aimed to establish the profile of such a patient, presenting the psychological factors that influence the reasons for which an elderly person might ask for dental treatment, as well as the general and the oral-dental morbidity in this age group. All these elements are necessary for adjusting the way in which a dentist works with the elderly or within a retirement home.